Analisis Penerapan Tata Kelola Perusahaan dan Audit Internal Terhadap Kinerja Keuangan Perbankan Syariah Indonesia - Febri Rikasari; Widhian Hardiyanti (Politeknik Ganesha Medan, 2022)
The world of banking is one of the important aspects in moving activities in the economic field. It is important for banks to maintain stable and increasing profitability to fulfill obligations to shareholders, attract investors to invest, and increase public confidence in storing excess funds held by banks. This study aims to analyze the effect of Corporate Governance by measuring the sharia supervisory board, board of directors, and audit committee on the financial performance of Islamic banking as measured by profitability using Return On Assets (ROA) in Islamic banking companies registered with the Financial Services Authority (OJK) for the periode 2017-2021. This research method uses secondary data with documentation techniques. With a population of 14 Islamic Comercial Banks, the sample for this study was 5 Islamic comercial bank companies that match the criteria for selecting each company that attaches financial statements and good corporate governance reports by including the number of sharia supervisory boards, boards of directors, and audit committees. The sampling method used in this research is using purposive sampling technique. The data analysis technique uses multiple regression analysis using the SPSS 25 program. The result of this study explain that the sharia supervisory board has a partial negative effect on profitability, while the board of directors and audit committee have no effect on profitability.